2011
DOI: 10.1007/s12105-011-0247-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Host Response to Oral Squamous Cell Carcinoma: An Adaptive T-Cell Response at the Tumor Interface

Abstract: Lymphocytic host response (LHR) in the RiskModel is histologically quantified as the density of lymphocytes at the tumor interface (Brandwein-Gensler in Am J Surg Pathol, 34:676-688, 1; in, Am J Surg Pathol 29:167-178, 2). It is classified as strong, intermediate or weak, and is inversely associated with the risk of decreased time to disease progression. In this study, we test the hypothesis that strong LHR corresponds to a greater degree of adaptive cytotoxic T cell response as compared to moderate LHR. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…LHR assessment presently does not require quantification of specific lymphocyte populations, however we have previously demonstrated that T cells are the predominant lymphocyte at the tumor advancing edge [23]. Figure 4a demonstrates a carcinoma with strong LHR throughout the advancing tumor interface.…”
Section: Resultsmentioning
confidence: 99%
“…LHR assessment presently does not require quantification of specific lymphocyte populations, however we have previously demonstrated that T cells are the predominant lymphocyte at the tumor advancing edge [23]. Figure 4a demonstrates a carcinoma with strong LHR throughout the advancing tumor interface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to dysfunctional T cells, decreased expression of major histocompatibility complexes (MHC), called HLA in humans, may also help the tumor cells evade adaptive immunity. MHC class I is essential for presenting peptides to CD8 + T cells and for CD8 + cytotoxic T lymphocytes (CTL) to recognize tumor cells expressing tumor‐associated or tumor‐specific antigens 50 . About 50% of HNSCC tumors might evade immune surveillance through the downregulation of MHC class I molecules 38 .…”
Section: T Cellsmentioning
confidence: 99%
“…35,51,52 Enhanced local adaptive immunity is known to have a protective impact on outcome in oral cavity squamous cell carcinoma and directly associates with cytotoxic CD8 cells. 3,4,53 Here we show that HPV16/18 in oral cavity squamous cell carcinoma is not associated with enhanced local adaptive immunity. In contrast, we and others have demonstrated enhanced local immune response in HPV-mediated oropharyngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 58%